Genetic analyses reveal promiscuous mating in female common minke whales, Balaenoptera acutorostrata - Skaug , Hans J.; Berube, Martine; Rew, Mary Beth; Palsboll, Per J. (J. Cetacean Res. Manage., 2023)
Based on 25 microsatellites, first order relatedness was established for three dyads of individuals contained in the Norwegian minke whale DNA-register. One large female minke whale was a member of all three dyads. Two competing genealogies were considered and under both of these the quartet contained siblings that with high probability must be half-siblings, as opposed to being full siblings.